Attention! Careful! Tutors wanted (Journal of Parents and Teachers, 2014)
Tutors live intensely educational relationships with children and families. They are specialists in some skills and attitudes like: accompany, trust, help, teach, discuss, encourage, manage conflicts. The preamble to the new education law -LOMCE- enlightens us to understand some educational aspects discussed in the media and society. Tutors and families collaborate together with bounty, to continue to meet the personal and educational needs of those people we call young age children and adolescents.
Keywords: education; teachet; tutor; relationship; students; families; attention; care; growth; dialogue; confidence; talent; learning; intelligences; skills; collaboration; love; bounty